The Pretreatment Systemic Inflammatory Response is an Important Determinant of Poor Pathologic Response for Patients Undergoing Neoadjuvant Therapy for Rectal Cancer - Dreyer, Stephan B. (Ann Surg Oncol, 2016)
BACKGROUND: Not all patients respond equally to neoadjuvant chemoradiotherapy (nCRT), with subsequent effects on survival. The systemic inflammatory response has been shown to predict long-term outcomes in colorectal cancer. The current study examined the association between systemic inflammation and nCRT in patients with rectal cancer. METHODS: Between 1999 and 2010, patients who underwent nCRT were identified. Serum measurements of hemoglobin, C-reactive protein, albumin, modified Glasgow prognostic score (mGPS), and differential white cell counts were obtained before and after nCRT. The Rödel scoring system measured pathologic tumor regression, and magnetic resonance imaging and computed tomography determined radiologic staging. RESULTS: The study included 79 patients. Of these patients, 37% were radiologically downstaged, and 44% were categorized as showing a good pathologic response (Rödel scores 3 and 4). As a validated measure of the systemic inflammatory response, mGPS (P = 0.022) was associated with a poor pathologic response to nCRT. A radiologic response was associated with a good pathologic response to treatment (P = 0.003). A binary logistic regression model identified mGPS (odds ratio [OR] 0.27; 95% confidence interval [CI] 0.07–0.96; P = 0.043) and radiologic response (OR 0.43; 95% CI 0.18–0.99; P = 0.048) as strong independent predictors of a pathologic response to treatment. CONCLUSION: The current study showed that a systemic inflammatory response before nCRT is associated with a poor pathologic response. Further study in a prospective controlled trial setting is warranted.